Intimacy, Individuation, and Marriage - Berezowsky, Janet (Canadian Journal of Counselling and Psychotherapy, 2012)
Self-differentiation and intimacy are fundamental issues in family functioning. The way in which couples deal with these tasks will significantly influence personal satisfaction and mutual commitment to growth in their relationship. The relationship of intimacy and individuation in marriage is paradoxical. Mates cannot achieve one without developing the other. However, in order to achieve either they must focus on process in the relationship. Intimacy and self-differentiation are by-products ofsuccessful process. In working with families it is important to distinguish process and outcome. Likewise it is important to distinguish between adaptation and growth goals. Intimacy and individuation will follow if we can facilitate process in the marital relationship.